Conversion of crude Jatropha curcas seed oil into biodiesel using liquid recombinant Candida rugosa lipase isozymes. (September 2015) - Kuo, Ting-Chun; Shaw, Jei-Fu; Lee, Guan-Chiun
Highlights: Recombinant CRL2 isozyme efficiently converted crude Jatropha oil into biodiesel. Optimum reaction parameters of the liquid CRL2-based process were determined. CRL2 isozyme achieved 95.3% of FAME yield in a methanol feed-batch process. Liquid CRL2 retained 53.0% of FAME yield after 3 reuse cycles for 6 days. Abstract: The versatile Candida rugosa lipase (CRL) has been widely used in biotechnological applications. However, there have not been feasibility reports on the transesterification of non-edible oils to produce biodiesel using the commercial CRL preparations, mixtures of isozymes. In the present study, four liquid recombinant CRL isozymes (CRL1–CRL4) were investigated to convert various non-edible oils into biodiesel. The results showed that recombinant CRL2 and CRL4 exhibited superior catalytic efficiencies for producing fatty acid methyl ester (FAME) from Jatropha curcas seed oil. A maximum 95.3% FAME yield was achieved using CRL2 under the optimal conditions (50 wt% water, an initial 1 equivalent of methanol feeding, and an additional 0.5 equivalents of methanol feeding at 24 h for a total reaction time of 48 h at 37 °C). We concluded that specific recombinant CRL isozymes could be excellent biocatalysts for the biodiesel production from low-cost crude Jatropha oil.